2013
DOI: 10.1071/py11052
|View full text |Cite
|
Sign up to set email alerts
|

Constant connections: piloting a mobile phone-based peer support program for Nuer (southern Sudanese) women

Abstract: Refugee women have poor psychosocial health as a result of past trauma and difficulties associated with settlement. This study was a pilot to find out how to use mobile phone-based peer support to improve the psychosocial health of, and facilitate settlement in a group of nine Nuer refugee women in Melbourne, Australia. Nine participants recruited by a community leader received peer support training over two five-week periods. They were further provided with mobile phone recharge vouchers to call one another t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(86 citation statements)
references
References 17 publications
1
85
0
Order By: Relevance
“…• Potential challenges presented by these new technologies (issues of privacy, confidentiality and possible surveillance and concerns over T A B L E 1 Search terms used in the scoping review Technology Relationship Service user "mobile phone" OR "mobile device" OR "mobile communication" OR "mobile technolog*" OR "mobile media" OR "cell* phone" OR "cell* device" OR "cell* communication" OR "communication technolog*" OR "cell* technolog*" OR "cell* media" OR smartphone OR "social media" OR "personal communication device" the unregulated development of "apps" or applications that can be used by phones) Interventions focusing on peer support reported positive benefits (Barlott et al, 2015;Hackett, Johnson, Shaw, & McDonagh, 2005;Walker et al, 2015;Wollersheim, Koh, Walker, & Liamputtong, 2013). While there were examples in many of these studies of participants for whom the intervention was less effective, only Daker-White and Rogers (2013) reported overall negative results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Potential challenges presented by these new technologies (issues of privacy, confidentiality and possible surveillance and concerns over T A B L E 1 Search terms used in the scoping review Technology Relationship Service user "mobile phone" OR "mobile device" OR "mobile communication" OR "mobile technolog*" OR "mobile media" OR "cell* phone" OR "cell* device" OR "cell* communication" OR "communication technolog*" OR "cell* technolog*" OR "cell* media" OR smartphone OR "social media" OR "personal communication device" the unregulated development of "apps" or applications that can be used by phones) Interventions focusing on peer support reported positive benefits (Barlott et al, 2015;Hackett, Johnson, Shaw, & McDonagh, 2005;Walker et al, 2015;Wollersheim, Koh, Walker, & Liamputtong, 2013). While there were examples in many of these studies of participants for whom the intervention was less effective, only Daker-White and Rogers (2013) reported overall negative results.…”
Section: Resultsmentioning
confidence: 99%
“…Wollersheim et al. 's () pilot and Walker et al. 's () subsequent study reported an intervention providing peer support training and mobile phones with free calls to refugee women who had migrated to Australia.…”
Section: Discussion: a Potential Typology Of Mobile Phone Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Refugee research literature has some examples of the effectiveness of utilizing peer support groups. Successful peer support models have been used to improve the perceived mental health of refugees and immigrants, and to aid them in their resettlement process [8,37]. Wollersheim et al [37] found that sharing of experiences and information via improved mobile phone communications enhanced the psychosocial wellbeing of a group of nine Sudanese female refugees.…”
Section: Opportunities For Peer Support For Antenatal Healthmentioning
confidence: 99%
“…Successful peer support models have been used to improve the perceived mental health of refugees and immigrants, and to aid them in their resettlement process [8,37]. Wollersheim et al [37] found that sharing of experiences and information via improved mobile phone communications enhanced the psychosocial wellbeing of a group of nine Sudanese female refugees. Likewise, peer-topeer workshops conducted among West African refugees in Australia were found to be effective in improving community knowledge regarding HIV and sexual health [8].…”
Section: Opportunities For Peer Support For Antenatal Healthmentioning
confidence: 99%